2011
DOI: 10.1080/15295192.2011.539503
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Parental Affect and Parenting Behaviors: A Meta-Analytic Review

Abstract: SYNOPSISObjective. The goal of the present investigation was to provide a meta-analytic review of the research on affect and parenting in nonclinical samples. Design. The authors conducted analyses on the overall mean effect size for 63 studies (k = 18,211). Affect was coded as either positive or negative, and parenting behavior was coded as either supportive-positive or harsh-negative. Moderators included definition of affect, time frame of measurement, reporter, child age, and parent gender. Results. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 80 publications
13
126
1
6
Order By: Relevance
“…Results suggesting that relational frustration was more strongly associated with parenting stress and child behavior problems than parent-reported attachment quality, confidence, discipline practices, or involvement, also underscore the particular significance of parental negativity and dyadic conflict to the processes under examination. This is consistent with existing studies demonstrating robust associations between parent negativity and criticism and problematic outcomes for children with DD (Carson and Parke 1996;Lovejoy et al 2000;Luoma et al 2004;Rueger et al 2011). Although this is the first known study to evidence parent-child relational frustration as a mechanism through which parenting stress influences child behavior, it is worth noting the context of our findings within a framework of parental role or relational satisfaction as well.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results suggesting that relational frustration was more strongly associated with parenting stress and child behavior problems than parent-reported attachment quality, confidence, discipline practices, or involvement, also underscore the particular significance of parental negativity and dyadic conflict to the processes under examination. This is consistent with existing studies demonstrating robust associations between parent negativity and criticism and problematic outcomes for children with DD (Carson and Parke 1996;Lovejoy et al 2000;Luoma et al 2004;Rueger et al 2011). Although this is the first known study to evidence parent-child relational frustration as a mechanism through which parenting stress influences child behavior, it is worth noting the context of our findings within a framework of parental role or relational satisfaction as well.…”
Section: Discussionsupporting
confidence: 78%
“…Evidence that parents' internal emotional experience during interactions with their children plays an important role in the unfolding of dynamic interpersonal processes consistent with a host of literature suggesting the centrality of emotional experiences and affective quality of parent-child interaction to child and family wellbeing in populations with and without DD (Landry et al 2001;Lovejoy et al 2000;NICHD 2004;Rueger et al 2011;Wiggins et al 2009). Additionally, increased negative affective experiences among parents of children with disabilities may be predictive of lower parenting satisfaction and decreased social competence among children over time (Carson and Parke 1996;Hanson and Hanline 1990).…”
Section: Discussionmentioning
confidence: 62%
“…It has also been suggested that the elevated risk of maternal depression and other mood disorders as a consequence of child maltreatment may contribute to negative effects in the subsequent generation, particularly given the robust body of literature linking hostile parenting to caregiver negative affect states, including depression (Heim & Nemeroff, 2001; Rueger, Katz, Risser, & Lovejoy, 2011). Children with depressed mothers have significantly higher rates of internalizing symptoms relative to children whose mothers are not depressed (Connell & Goodman, 2002; Goodman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dix, 1991;Lovejoy et al 2000). Parents who score low on positive affect may interact less with their children or their interactions may have a 'flat tone' but probably they are not hostile or coercive, while parents scoring high on negative affect may be intrusive and excessively critical (Rueger et al 2011). Poor emotion regulation is also common in individuals who suffer depression.…”
mentioning
confidence: 99%